Solutions to Improving the Performances and Emission Control in a Poor Mixtures Fueled Automotive Spark Ignition Engine. (2016) - Rakosi, Edward; Talif, Sorinel Gicu; Manolache, Gheorghe
Abstract: This paper is a synthesis of some theoretic and experimental researches done during several years, in order to find the most efficient and simple solutions for changing some automotive spark ignition engines that work on homogeneous mixtures to those that function on inhomogeneous poor mixtures, using the gasoline injection. The paper also presents the premises and the ways of achieving at this solution that uses mainly the centrifugal action of the mixture obtained in a cylinder.